2018
DOI: 10.1088/1741-4326/aaaa9b
|View full text |Cite
|
Sign up to set email alerts
|

Observation of multi-channel non-local transport in J-TEXT plasmas

Abstract: In cold pulse experiments in J-TEXT, not only are rapid electron temperature increases in core observed, but also steep rises of inner density are found. Moreover, some evidence of acceleration of the core toroidal rotation is also observed during the non-local transport process of electron temperature. These new findings of cold pulse experiments in J-TEXT suggest that turbulence spreading is possible mechanism for the non-local transport dynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…In a nutshell, in most of the previous experimental research, the NLT phenomenon in the cold pulse experiment has only reported and focused on the electron heat transport channel. However, our research results in J-TEXT show that NLT effects also exist in particle transport channel [17]. The rotation or momentum transport also has some possible NLT response in the cold pulse experiment [17].…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…In a nutshell, in most of the previous experimental research, the NLT phenomenon in the cold pulse experiment has only reported and focused on the electron heat transport channel. However, our research results in J-TEXT show that NLT effects also exist in particle transport channel [17]. The rotation or momentum transport also has some possible NLT response in the cold pulse experiment [17].…”
mentioning
confidence: 66%
“…However, our research results in J-TEXT show that NLT effects also exist in particle transport channel [17]. The rotation or momentum transport also has some possible NLT response in the cold pulse experiment [17]. Recently, the temporal resolution of the diagnostic systems for ion temperature measurement in J-TEXT is upgraded to millisecond level, which provides us with the capability to investigate the dynamic response of ion transport channel in the cold pulse experiment.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…One of the perplexing phenomena observed and extensively studied worldwide is non-local transport, which has been investigated in various tokamaks (TFTR, [1] TEXT [2] /J-TEXT, [3] , RTP, [4,5] HL-2A, [6] Alcator C-mod, [7] KSTAR, [8] EAST, [9] Tore Supra, [10] JET, [11] AUG, [12] DIII-D [13] ) and stellerators(W7-AS, [14] LHD [15] ). These experiments have consistently revealed a peculiar long-range transient temperature response triggered by pulsed interventions.…”
Section: Introductionmentioning
confidence: 99%